PENERAPAN FRAMEWORK CODEIGNITER PADA PEMBANGUNAN SISTEM INFORMASI AKADEMIK DI UNIVERSITAS SAHID SURAKARTA - Taufiq Dio Eka Putra; Hardika Khusnuliawati; Arif Nugraha Hernanjaya (Universitas Sahid Surakarta, 2018)
Sahid Surakarta University has about 950 students and 66 lecturers in 2017, of hich the number is relatively large compared to the number of staff employees. TheUniversity of Sahid Surakarta also does not have a computerized study plan card system in 2017. Web Based Study Card Study Information System with codeigniter framework at the University of Sahid Surakarta is an information system that provides data processing academic schedule, Study Plan Card (Kartu Rencana Studi) and Result Study Card (Kartu Hasil Study) student registration. The final result of this final project is Study Plan Card Information System Sahid Surakarta University which can be used as computerized system to support the administrative process of university employees in processing schedule data, Study Plan Card, Study Result Card, and as media ofinformation summary for university leader.